Rate and Extent of Growth of a Model Extremophile, Archaeoglobus fulgidus, Under High Hydrostatic Pressures - Oliver, Gina C.; Cario, Anaïs; Rogers, Karyn L. (Frontiers in Microbiology, 2020)
High hydrostatic pressure batch cultivation of a model extremophile, Archaeoglobus fulgidus type strain VC-16, was performed to explore how elevated pressures might affect microbial growth and physiology in the deep marine biosphere. Though commonly identified in high-temperature and high-pressure marine environments (up to 2-5 km below sea level, 20-50 MPa pressures), A. fulgidus growth at elevated pressure has not been characterized previously. Here, exponential growth of A. fulgidus was observed up to 60 MPa when supported by the heterotrophic metabolism of lactate oxidation coupled to sulfate reduction, and up to 40 MPa for autotrophic CO2 fixation coupled to thiosulfate reduction via H2. Maximum growth rates for this heterotrophic metabolism were observed at 20 MPa, suggesting that A. fulgidus is a moderate piezophile under these conditions. However, only piezotolerance was observed for autotrophy, as growth rates remained nearly constant from 0.3 MPa to 40 MPa. Experiments described below show that A. fulgidus continues both heterotrophic sulfate reduction and autotrophic thiosulfate reduction nearly unaffected by increasing pressure up to 30 MPa and 40 MPa, respectively. As these pressures encompass a variety of subsurface marine environments, A. fulgidus serves as a model extremophile for exploring the effects of elevated pressure on microbial metabolisms in the deep subsurface. Further, these results exemplify the need for high-pressure cultivation of deep-sea and subsurface microorganisms to better reflect in situ physiological conditions.